Fabric phase sorptive extraction combined with gas chromatography-mass spectrometry as an innovative analytical technique for the determination of selected polycyclic aromatic hydrocarbons in herbal infusions and tea samples. Issue 12 (1st March 2022) - Manousi, Natalia; Kabir, Abuzar; Furton, Kenneth G.; Rosenberg, Erwin; Zachariadis, George A.
Abstract : A fabric phase sorptive extraction (FPSE) protocol for the isolation and preconcentration of four selected polycyclic aromatic hydrocarbons from tea samples and herbal infusions is presented, followed by their quantitative analysis by GC-MS. Abstract : This study presents a fabric phase sorptive extraction (FPSE) protocol for the isolation and preconcentration of four selected polycyclic aromatic hydrocarbons from tea samples and herbal infusions, followed by their separation and quantification by gas chromatography-mass spectrometry (GC-MS). In FPSE, extraction of the target analytes is performed utilizing a flexible fabric substrate that is coated with a highly efficient sol–gel sorbent. In this work, eighteen different FPSE membranes were examined, with the highest extraction recoveries being observed with the sol–gel C18 coated FPSE membrane. The main parameters that influence the adsorption and desorption of the PAHs were optimized and the proposed method was validated. The detection limits and the quantification limits were 0.08–0.17 ng mL −1 and 0.25–0.50 ng mL −1, respectively, for the different target compounds with a 10 mL sample. The relative standard deviations for intra-day and inter-day repeatability were less than 7.9% and 8.5%, respectively. The sol–gel C18 coated FPSE membrane could be used for at least 5 subsequent sample preparation cycles. Finally, the proposed protocol was successfully employed for the determination of PAHs in a wide range of tea and herbal infusion samples.